ANALISIS PROFIL BERKAS RADIASI LINEAR ACCELERATOR 6MV PADA PENGGUNAAN VIRTUAL WEDGE DENGAN GAFCHROMIC FILM - Arisa Dwi Sakti; Eko Hidayanto; Heri Sutanto; Sanggam Ramantisan (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
Analysis of the radiation beam profile linear accelerator 6mV on the use of virtual wedge with gafchromic film done as a virtual wedge calibration on the linear accelerator . Virtual wedge calibration was originally done using ionization chamber detector, but its use is not efficient because for one-time calibration with an area of 10 x 10 cm2 field takes 10 times the exposure with the results of 10 data transform one dose profile curve . It takes a dosimeter that can capture the entire virtual dose results wedge with one exposure is gafchromic films with an area that can be customized . This research was conducted with a virtual wedge on the Siemens PRIMUS linear accelerator , scanner Epson Stylus 10000 XL , Solid Water Phantom , Matlab Program and Excel Program. This research begin to find the corelation between radiation beam and pixel value on gafchromic film with field size 1x 1 cm2. This corelation in used to find profile dose of virtual wedge from gafchromic film with field size 1 x 11 cm2. Variation fof gafchromic film is in this angle on 150, 300, and 450, opening jaws in Y1and Y2and teh last variation of half beam position in (-10 until 0),(-5 until 5) and (0 until 10). This research find that in higher beam dose, make the darkness film but lowerpixel value.ther are 2 corection in jaws position Y2 half beam (-10 until 0)300 and jaws position Y2 half beam (0 until1 0) 450. No one of ymetrisity value higher than 3% appropriate with AAPM TG-47.Keyword: virtual wedge, profil dosis, gafchromicf film, half beam